PRE-WAR STATE OF DOMESTIC PIG BREEDING - Povod, M.; Andrieieva, D.; Lykhach, A.; Deschenko, O.; Lykhach, V.; Reznichenko, V.; Bondarskaya, O. (Scientific Progress & Innovations, 2022)
The article presents the results of the analysis of the current, pre-war state of domestic pig breeding as an important industry in the general structure of agricultural production in the country. Data on the state of the pig industry in Ukraine from 1981 to 2020 are taken into account and analyzed. The solution to the problem of increasing meat production and increasing the level of meat supply to the population largely depends on the development of pig breeding, the features of which make it possible to increase the number of pigs in the shortest possible time and achieve the required meat production. After all, in crisis situations, pig breeding often became the main source of rapid growth in meat production. In addition, pig breeding is one of the key branches that provide Ukraine with meat and fat products. In Ukraine, it is represented by producers of two categories – the homestead sector and industrial pig farms. There is a sharp decline in the number of pigs in the homestead sector, in contrast to the industrial sector. The number of pigs in Ukraine changed in different ways, the main reasons for the significant reduction in the number of pigs in the country include the disparity in prices for agricultural and industrial products; raise in feed prices; the inability of most domestic producers to use the latest technologies for keeping and fattening pigs; liquidation of specialized pig farms (up to 300 sows); saturation of the domestic market with raw materials of foreign production; reduction of state support; complications of the epizootiology situation (ASF); a difficult economic situation of ordinary Ukrainians. During the analyzed years, the least pork was produced in 2020, where the main reason for this phenomenon was adverse weather conditions and the global and national economic crisis caused by the massive pandemic of the coronavirus COVID-19. At the present stage in Ukraine the task is to radically revive the pig industry and transfer it to industrial technology, as well as to ensure that it can provide cheap, high quality and competitive products. To do this, our country has the necessary breeding gene pool and breeding base of pigs, fertile land to form an appropriate fodder base, as well as a highly qualified potential of scientists and producers for the rational management of the pig industry.